The Effect of Workload, Work Environment, Individual Factors and Work Motivation on Work Stress of Health Workers at Pratama Nurjaya Clinic - Silvania, Grace Ayu; Bagenda, Wahyuddin; Widjaja, Yani Restiani (Journal of Economics and Social Sciences (JESS), 2025)
The purpose of this study is to determine the influence of workload, work environment, individual factors and work motivation on work stress of health workers. The research population was 33 health workers. The sampling technique used is to include all health workers at the Pratama Nurjaya Clinic, namely by census. This type of research is quantitative research. The statistical instrument used was multiple regression analysis using validity, reliability and classical assumption tests. Based on the results of the study, it was found that there was an influence between workload (p = 0.022), work environment (p = 0.007) and work motivation (p = 0.030) on the work stress of health workers partially and it was found that there was no influence of individual factors (p = 0.343) on work stress. The most dominant factor affecting work stress is the work environment.